Efektivitas Kinerja Pegawai Subdit Gakkum Polda Jatim dalam Pelayanan Konfirmasi dan Pengecekan Tilang bagi pengendara pada Program ETLE (Electronic Traffic Law Enforcement) - Fauzia Salsabila Rahma; Hendra Wijayanto (VISA: Journal of Vision and Ideas, 2026)
The implementation of ETLE (Enforcement of Electronic Traffic Law Enforcement) is a form of digital transformation in traffic law enforcement aimed at increasing the transparency and effectiveness of public services. The success of this program is determined not only by technological sophistication but also by the performance of employees managing the ticket confirmation and verification process. This study aims to assess the effectiveness of the performance of employees at the East Java Regional Police's Sub-Directorate of Law Enforcement (Sub-Directorate of Law Enforcement) in providing electronic ticket confirmation and verification services to the public. The research method used was a qualitative case study approach. Data collection techniques included non-participatory observation, unstructured interviews, and documentation. The analysis of employee performance success is based on Richard M. Steers' theory of organizational effectiveness, which encompasses goal achievement, integration, and adaptation. The results indicate that the performance of employees at the East Java Regional Police's Sub-Directorate of Law Enforcement (Sub-Directorate of Law Enforcement) is quite effective. Employees are able to meet service time targets as stipulated, maintain accuracy in administrative verification, and provide explanations and assistance to members of the public experiencing difficulties understanding the system. Furthermore, cooperation among employees and the ability to adapt to increasing workloads and technological developments contribute to smooth service delivery. Despite challenges such as the increasing number of violation data and the unequal public understanding of the program, employee performance has generally been good in supporting the system's implementation.